2017
DOI: 10.1515/polyeng-2015-0427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of screw configuration on the dispersion of nanofillers in thermoset polymers

Abstract: Abstract This paper deals with the study of screw configuration for dispersing nanofillers in thermoset polymers using an intermesh co-rotating twin screw extruder. The influence of kneading elements on the dispersion of nanoclay in epoxy was examined using 10 different screw configurations. Nanoclay was dispersed in epoxy at a barrel temperature of 5°C and a screw speed of 100 rpm. The combination of right hand kneading block and three/four lobed kneading blocks resulted in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…There are many different types of elements for screws, with different parameters as root, crest, flank, angle flank, and pitch (see more in Ref. ) and the screw is common designed considering the type of polymer. This screw configuration was designed and keeping for direct blending and masterbatch process of HDPE.…”
Section: Methodsmentioning
confidence: 99%
“…There are many different types of elements for screws, with different parameters as root, crest, flank, angle flank, and pitch (see more in Ref. ) and the screw is common designed considering the type of polymer. This screw configuration was designed and keeping for direct blending and masterbatch process of HDPE.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Kumar et al [17] manufactured the epoxy/Al 2 O 3 nanocomposites by the solution process and practically reported that the filling of nanoparticles altered the arrangement of nanocomposites. Shafi et al [18, 19] evaluated the consequence of nanoclay addition on fatigue properties of carbon fibre-reinforced epoxy composites, found improved mechanical properties of epoxy nanocomposites than that of neat epoxy resin and also observed inadequate shearing fallouts into agglomerations. Rice et al [20] did not observe any significant improvements in the mechanical properties of carbon fibre-reinforced laminates of epoxy.…”
Section: Introductionmentioning
confidence: 99%